(3CSGSjGJ GdGbJUGO GdSjGSjs - (3YGOd GMeO(B, (3MTjTs; (3eLOj eMehO(B, (3TgGH hBNQhfs ((3dHfGf(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2003)
(3Yde GdGbJUGO WQb h COhGJ GdJMdjd GdGbJUGOj h GdJMdjd GdGbJUGOj GdLRFj , eaghe GdGfJGL h YfGUQg , GdfGJL Gdbhej h GdONd Gdbhej Hjf GdGSJgdGc h GdGONGQ h GdGSJKeGQ , Gdgjcd GdJfXjej h GdfXGe GdGbJUGOj , GdKef h GdShb h GdYdGbGJ GdOGdjI , GdWdH h GdYQV h eQhfJgeG Sdhc GdeSJgdc h GdJMdjd HGdefaYI GdMOjI , Sdhc GdeSJgdc h GdJMdjd HefMfjGJ GdShGA , GdJMdjd HbGfhf GdfSH GdeJZjQI , Sdhc GdeTQhY aj Shb GdefGaSI GdcGedI h aj Shb GMJcGQ GdHjY , hCNjQG CSGSjGJ fXQjI GdJhRjY(B.s
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdSjGSjs; (3GdJMdjd GdGbJUGOjs